Lackey gains co-op presidency - Mullings, David (Raton Range Raton, New Mexico, 1984)
Newspaper Article on Raton's John Lackey becoming president of Arkansas River Power Authority in Colorado.
Master list item #: 1
File location is in the Raton File Cabinet
Keywords: Lackey, John; Baker, George; Henderson, Jim; Reichard, Joe; Robertson, Gordon; Colorado political subdivision; Arkansas River Power Authority; Raton Public Service Company; Western Area Power Administration; Local History; Biography; Company presidency; Career; Life and Customs; Raton, New Mexico; La Junta, Colorado; Springfield, Colorado; Walsenburg, Colorado; Lamar, Colorado; Las Animas, Colorado; Trinidad, Colorado